Mengeksplorasi Argumentasi dan Pengetahuan Pendidik Ilmu Pengetahuan Alam (IPA) Tentang Pemanasan Global: Exploring the Arguments and Knowledge of Natural Sciences (IPA) Educators on Global Warming - Septaria, Kiki (Universitas Muhammadiyah Sidoarjo, 2019)
This research isa qualitative research based oncasestudiestoinvestigatethe quality ofthe arguments and personal knowledge of scienceteachers about global warming. Thesubjects ofthis research were 20scienceteachersfromthesamestudy program and university. Data collectiontechniques use interview methods and written arguments. Qualitative analysis of datafrom interviews and written arguments reveals thatsomescienceteachers use evidence during argumentation, butthe evidence used is often not accurate enoughtosupport or refute other people's claims or arguments andsome otherscience teachers use personal perspectivesin argumentation becausescienceteachers have difficulty building evidence-based argumentation. In addition, somescienceteachers have similarities inknowledge about global warming, butthere aresomescienceteachers who differ intheir belief inscientific expertise and thecredibility of scientific evidence. This research is expectedto help increasetheknowledge andskills ofscience teachersto educate global warmingto students and prepare studentsto makethe right decisions about global warming in the future.